2005
DOI: 10.1074/jbc.m507198200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with PDZ Domain Proteins PIST/GOPC and PDZK1 Regulate Intracellular Sorting of the Somatostatin Receptor Subtype 5

Abstract: By yeast two-hybrid screening we have identified interaction partners for the intracellular C-terminal tail of the human and rodent somatostatin receptor subtype 5 (SSTR5). Interactions with the PDZ domain-containing proteins PIST and PDZK1 are mediated by the PDZ ligand motif at the C terminus of the receptor; in case of the human and mouse (but not the rat) receptors, a slight sequence variation of this motif also allows for binding of the peroxisomal receptor PEX5. PIST is Golgi-associated and retains SSTR5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(90 citation statements)
references
References 46 publications
7
82
0
Order By: Relevance
“…Wente et al identified two PDZ-domain containing proteins PIST and PDZK1, which interact with the C-terminus of sst 5 and seem to regulate its intracellular transport (Wente et al, 2005). Remarkably, all sst subtypes have a PDZ-binding motif in the C-terminal tail (Wente et al, 2005).…”
Section: Somatostatin Receptor Subtype 5 (Sst 5 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Wente et al identified two PDZ-domain containing proteins PIST and PDZK1, which interact with the C-terminus of sst 5 and seem to regulate its intracellular transport (Wente et al, 2005). Remarkably, all sst subtypes have a PDZ-binding motif in the C-terminal tail (Wente et al, 2005).…”
Section: Somatostatin Receptor Subtype 5 (Sst 5 )mentioning
confidence: 99%
“…Remarkably, all sst subtypes have a PDZ-binding motif in the C-terminal tail (Wente et al, 2005). PIST is a Golgi apparatus associated protein and colocalizes with sst 5 in mouse pituitary AtT-20 cells.…”
Section: Somatostatin Receptor Subtype 5 (Sst 5 )mentioning
confidence: 99%
“…However, the similar characteristics between the last four amino acids of ␤2AR and CCR5 led us to suggest that the SVGL motif of CCR5 could act as a "recycling signal." Such a "recycling signal" is also found in other GPCRs, such as human lutropin receptor (Galet et al, 2004), -opioid receptor (Tanowitz and von Zastrow, 2003), D1 dopamine receptor (Vargas and Von Zastrow, 2004), endothelin receptor A (Paasche et al, 2005), and somatostatin receptor 5 (Wente et al, 2005). Whatever the recycling signal, they all share a leucine and/or a phosphate acceptor.…”
Section: Discussionmentioning
confidence: 95%
“…Likewise, the sorting protein is also different from one GPCR to another (Cao et al, 1999;Whistler et al, 2002;Wente et al, 2005). Many PDZ domain-containing proteins interact with GPCR C termini (Bockaert et al, 2003); some of them have been identified as being involved in GPCR postendocytic trafficking (Trejo, 2005).…”
mentioning
confidence: 99%
“…Comparable to CFTR, both the beta1-adrenergic receptor and cadherin 23 interact with CAL, leading to their intracellular accumulation and/or degradation (Fig.2); these interactions can be competitively counteracted by binding with other PDZ domain-containing proteins (He et al, 2004;Xu et al, 2010). Likewise, CAL is an intracellular retention partner for the somatostatin receptor subtype 5 and the metabotropic glutamate receptor subtypes 1a (Wente et al, 2005;Zhang et al, 2008).…”
Section: Cal Targets Cftr To Lysosomal Degradationmentioning
confidence: 99%